Oncologic alert in dentist activity, algorithms for primary examination - Лісова, Ірина Григорівна; Фурніченко, Максим Павлович; Ковальчук, Валерія Володимирівна (Actual Dentistry, 2019)
Aim of the study: optimization of early detection of maxillofacial cancer by activation of oncostasis with identification of risk groups and improvement of algorithms of prophylactic oncological examinations based on the analysis of retrospective determination of features of cases of diseases. Materials and methods. Materials for this study were dispensary cases of patients with cancer of the maxillofacial region for 10 years. The frequency of cancer was determined with the localization, stage, neglect of diseases, taking into account the age and gender of patients. Research results. For 10 years 93 (100 %) of persons with malignant diseases of the maxillofacial area were on the dispensary account, among them men 76.34 % and 23.66 % women, mostly elderly and middle-aged. The data obtained showed a stable growth of malignant neoplasm of the maxillofacial area, the frequency of neglected forms of which increased by 2 times. It was registered with stage I cancer 22.58 %, from II – 33.33 %, from the II – 17.20 % and 26.88 % from the IV century. In 55.91 % of patients with lesions mostly easily accessible for examination was stage I and II stage cancer. In 44.1 % of patients were «neglected», stage III and IV stage disease with localization difficult to access. Successful early diagnosis of oncopathology depended on the quality of the medical examination. Provided oncologists with postulates and substantiated features of oncologic examination with the use of special techniques. Conclusions. 1) The results of numerous studies indicate an increase in Ukraine the number of patients with cancer of the face and jaw, which is due to a number of social and environmental factors. One of the aspects of the problem is the lack of routine preventive examinations and the low level of alertness among dentists. 2) A retrospective analysis of carcinogenesis of the maxillofacial region revealed age and gender features, they must be taken into account when forming risk groups and detailing the stages of the initial examination. 3) The progress of the stages of cancer is associated with the localization of the affected area and its accessibility for examination. This prompts the improvement of visual and manual techniques for oncological examination of the patient with subsequent orthopantomographic examination of the jaws. 4) Activation of cancer alertness in the activities of dentists and the effective use of inspection algorithms is possible when developing appropriate protocols and approving them by the Ministry of Health of Ukraine. Key words: neoplasm of maxillofacial area frequency and localization, oncological alert, dentists, algorithms of primary oncological examination